Sci-Hub, Knowledge, Information, Dentistry, Students, dental, Open access publishing - Cecilia Muñoz-Sandoval; Karla Gambetta-Tessini; Claudia Rodriguez-Jaque; Daniel Bravo-Cavicchioli; Rodrigo A. Giacaman (Universidad de Concepción., 2022)
Objetive: To evaluate microleakage of composite resins (CR) placed over different cavitary liners after managing deep caries lesions through selective removal of soft carious tissue to soft dentin (SRCT-S). Material and Methods: Fifty four human teeth were collected for microleakage testing. Each assay comprised ICDAS 5 or ICDAS 6 carious lesions and sound teeth for controls. Sound teeth were prepared with cavities that mirrored the carious teeth cavities, which were prepared with SRCT-S. Sound and carious teeth were further randomly assigned to one of the three experimental groups: Group A: universal adhesive (UA) + CR, Group B: glass ionomer cement liner + UA + CR, and Group C: calcium hydroxide + UA+ CR. Occlusal microleakage (OM) and cervical microleakage (CM) was classified within one of 5 depth categories. ANOVA and Chi-square tests were computed (p<0.05). Results: OM and CM were similarly distributed across subgroups (p>0.05). All Group C samples with carious lesions presented some degree of microleakage. However, no statistically significant differences were observed between groups and within each group (p>0.05). Conclusion: Teeth restored with CR after SRCT-S using calcium hydroxide as a liner material seem to exhibit higher microleakage than those restored using glass ionomer or UA alone. Further clinical research is needed to deepen these findings. Clinical significance: The application of calcium hydroxide as a liner under a composite resin may reduce the longevity of a restoration after performing selective or partial removal of carious tissues. Clinicians should rethink the need of using calcium hydroxide for this application, albeit the lack of clinical evidence.